FREQUENCY OF ABO AND Rh BLOOD GROUPS IN STUDENTS OF AKHTAR SAEED MEDICAL AND DENTAL COLLEGE, LAHORE - Kanwal, Shumaela; Qureshi, Hamid Javaid; Aslam, Muhammad Sohail; Masood, Shahroona (Pakistan Journal of Physiology, 2016)
Background: This study was conducted to find out the frequency of ABO and Rh blood groups and association of a specific blood group with a cast in students of this medical institution. Methods: It was a cross sectional study carried out in Akhtar Saeed Medical and Dental College, Bahria Town, Lahore. A total of 618 students participated in the study. Informed consent was taken from each participant of the study. Personal data of each participant including cast was recorded on a proforma. Blood groups were determined by slide test method using anti sera A, B and D. Results: The results of the study showed that blood group B was most common (40.45%) blood group followed by O (31.06%), A (20.38%) and AB (8.09%). Regarding Rh blood group, 89.48% of the students were Rh+. There was no gender difference in frequency of ABO and Rh blood groups. In Arian, Rajput, Jutt, Sheikh, Mughal and Baloch casts; blood group B+ was most common but in khans and Syeds, blood group O+ was most common. Conclusion: Blood group B+ is the most common blood group in the students of Akhtar Saeed Medical and Dental College and there is an association between a specific cast and blood group. In Khans and Syeds, blood group O+ is most common. Pak J Physiol 2016;12(1):29–30